2014
DOI: 10.1371/journal.pone.0095749
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variability in Metabolite Measurements from Urinary Samples

Abstract: BackgroundThe application of metabolomics in epidemiological studies would potentially allow researchers to identify biomarkers associated with exposures and diseases. However, within-individual variability of metabolite levels caused by temporal variation of metabolites, together with technical variability introduced by laboratory procedures, may reduce the study power to detect such associations. We assessed the sources of variability of metabolites from urine samples and the implications for designing epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Nevertheless, its integration into population-based research remains in its early stages (2). Rigorous methods studies identifying sources of variability in metabolite measurements for various types of biological specimens is critical (18, 32, 33). Presently, relatively few human studies have used untargeted metabolomics platforms to analyze fecal samples.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, its integration into population-based research remains in its early stages (2). Rigorous methods studies identifying sources of variability in metabolite measurements for various types of biological specimens is critical (18, 32, 33). Presently, relatively few human studies have used untargeted metabolomics platforms to analyze fecal samples.…”
Section: Discussionmentioning
confidence: 99%
“…plant-insect interactions | metabolomics | mass spectrometry | natural variation E lucidating the structure of metabolites underlying complex traits and the factors that maintain their variation in natural populations are important challenges in plant ecological studies (1). Many studies have notably shown that stress-responsive pathways that produce secondary metabolites are sporadically found across different plant taxa with extensive diversification (2).…”
mentioning
confidence: 99%
“…The following metabolites show higher concentrations in men than in women (also higher in high REE or LBM, respectively): creatinine, leucine, 4-deoxythreonic acid, and uric acid. These metabolites are either involved in muscle energy metabolism [13,16,18,47,48] and known to be determined by the larger muscle mass in men [49], or their function is yet unknown [19,50]. It is likely that sex differences cause a differential production of muscle-specific metabolites.…”
Section: Discussionmentioning
confidence: 99%